Trends in long‐term mechanical circulatory support for advanced heart failure in the UK. (October 2013) - Emin, Akan; Rogers, Chris A.; Parameshwar, Jayan; MacGowan, Guy; Taylor, Rhiannon; Yonan, Nizar; Simon, Andre; Tsui, Steven; Schueler, Stephan; Banner, Nicholas R.; ,; Banner, Nicholas; et al.
<x xml:space="preserve">Abstract</x> Aims Heart transplantation (HTx) is limited by the scarcity of suitable donor hearts. Consequently, more patients with advanced heart failure require a ventricular assist device (VAD). We report UK activity, trends, and outcome for long‐term VAD support as a bridging therapy to HTx. Methods and results Patients were grouped into three eras: E1, February 2004–March 2006; E2, April 2006–March 2009; and E3, April 2009–March 2011. Exclusions were patients who received isolated short‐term support or extracorporeal membrane oxygenation without prior or subsequent long‐term VAD support. A total of 247 patients received VAD support; 202 left ventricular (LVAD) support alone and 45 both left and right ventricular support. Activity increased over time, from 36 patients implanted in E1 to 123 in E3. Overall, 46 patients received a first‐generation device, 80 a second‐generation device, and 121 a third‐generation device. Use of third‐generation devices increased from <6% in E1 to 78% in E3. Median duration of LVAD support increased from 141 days in E1 to 578 days in E3 (P < 0.001). Overall survival to 1 year after LVAD implant rose from 58.3% [95% confidence interval (CI) 40.7–72.4%] in E1 to 72.5% (95% CI 63.3–79.8%) in E3 (P = 0.21), and improved significantly with device generation; at 1 year, 50% of patients with first‐generation devices were alive compared with 68.1% and 76.9% of patients with second‐ and third‐generation devices, respectively (P = 0.002). These differences remained after risk adjustment. HTx following LVAD implant reduced over time (P < 0.001). Conclusion VAD activity and duration of support have increased. There has been a shift from first‐ and second‐ to third‐generation devices, and an associated improvement in survival.